The Influence of Free Fire Online Gaming on Aggressive Behavior Among Vocational High School Students in Gowa, Indonesia - Ilham Nugraha; Amiruddin; Dwi Rezky Anandari Sulaiman (PT. Global Research Collaboration, 2026)
This study investigated the relationship between Free Fire online gaming intensity and aggressive behavior among vocational high school students in Gowa, Indonesia. Using a quantitative ex post facto correlational design, the study involved 42 Grade X and XI students from the Computer and Network Engineering program who actively played Free Fire. Data were collected through questionnaires, observation, and documentation. The research instruments demonstrated acceptable reliability, with Cronbach’s alpha coefficients of 0.750 for the online gaming variable and 0.809 for the aggressive behavior variable. The data were analyzed using descriptive statistics and simple linear regression. The results showed that Free Fire online gaming intensity was significantly associated with students’ aggressive behavior (p < .001). Students with higher gaming intensity tended to report stronger verbal aggression, irritability, and emotional reactions, particularly after defeat during gameplay. These findings indicate that intensive engagement with competitive online games may be linked to aggressive behavioral tendencies among vocational students. Schools and parents should provide guidance on healthy gaming habits, time management, and emotional regulation to minimize potential behavioral risks.